2021
DOI: 10.1186/s12913-021-07227-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ perceptions on medication communication challenges and solutions – text mining and manual content analysis - cross-sectional study

Abstract: Background Communication challenges contribute to medication incidents in hospitals, but it is unclear how communication can be improved. The aims of this study were threefold: firstly, to describe the most common communication challenges related to medication incidents as perceived by healthcare professionals across specialized hospitals for adult patients; secondly, to consider suggestions from healthcare professionals with regard to improving medication communication; and thirdly, to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study carried out in Spain that identifies the barriers and facilitators of communication for medication reconciliation from the perspective of primary healthcare professionals. The results obtained show, along the lines of other studies, that the challenges in communication can be interlevel, involving transitions between different levels of care [23,29]; among healthcare professionals involved in primary healthcare [22,37,38]; and between healthcare professionals and patients/caregivers [39,40].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study carried out in Spain that identifies the barriers and facilitators of communication for medication reconciliation from the perspective of primary healthcare professionals. The results obtained show, along the lines of other studies, that the challenges in communication can be interlevel, involving transitions between different levels of care [23,29]; among healthcare professionals involved in primary healthcare [22,37,38]; and between healthcare professionals and patients/caregivers [39,40].…”
Section: Discussionsupporting
confidence: 77%
“…Several authors have pointed out the need to redesign interprofessional work systems to improve patient follow-up [17] In this sense, and taking into account the statements of the participants in our study, this redesign could involve improving computerized clinical histories, and the protocolization of clinical sessions or meetings that can now be carried out via videoconferences and other telematic media with some ease; this has already been proven to be useful [17,22,29]. There is no doubt that, for this to happen, it is also necessary to adjust workloads and include this communication as another care task to be carried out by healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have frequently uncovered communication and coordination issues among healthcare professionals. 9 They further suggested that communication gaps between healthcare professionals could lead to medication errors 10 and discrepancies in treatment approaches due to insufficient interprofessional collaboration. 11 …”
Section: Introductionmentioning
confidence: 99%